STRATEGI PEMASARAN KAIN BATIK BENANG BINTIK KHAS KALIMANTAN TENGAH UNTUK MENARIK MINAT BELI KONSUMEN - Daisy Arimetha Dau; Lelo Sintani; Usup Riassy Christa (Media Bina Ilmiah, 2023)
Research in the field of marketing with a qualitative approach in increasing consumer purchase demand. SWOT analysis is used to be able to provide a descriptive picture of the marketing strategy. The research was conducted in depth on four batik business owners in Central Kalimantan. The results of the strategy show SO (Strength – Opportunities) as a marketing strategy, with the strengths that the organization has, it must be able to work on all the opportunities that are available outside. Marketing Relations with Government and Private Agencies related to the provision of Spotted Batik Yarn Fabrics, is one way of marketing to build and develop closer relationships with customers. The WO (Weakness – Opportunities) strategy which first fixes the weaknesses in the internal area so that you can work on the opportunities that exist outside. WT Strategy (Weaknesses – Threats). Which, to deal with the meeting area between weaknesses and threats is to control losses (damage control) so that the damage does not become more severe than expected. For further research this can be done on consumers regarding consumer buying interest quantitatively.